Relationship of surface roughness with current and voltage during wire EDM - Khan, Ahsan Ali; Mohd Ali , Munira; Shaffiar, Norhashimah (Asian Network for Scientific Information, 2006)
Wire EDM is in use for a long time for cutting punches and dies, shaped pockets and other machine parts. Surface finish of the machined surface mainly depends on current and voltage used during machining. In the present research experimental investigations have been conducted to establish relationships of job surface finish with current and voltage. Brass wires of diameters 0.3, 0.25, 0.20 and 0.15 mm were used. Work materials tested were mild steel, aluminum, cemented carbide, copper and stainless steel. After machining each material with specific current and voltage the hardness and the job surface roughness were measured and their surfaces were obsetved under an electron-scanning microscope. Results of the experiments show that in general the machined surface becomes rougher with increase in current and voltage. Microstructures of the specimens also show that craters on the finished surface become larger as a result of using higher current and voltage. It was also found that wires of smaller diameters give smoother surface than those cut with larger diameters. It has been established that machining of carbides should be limited to wires with diameter equal to or less than 0.15 mm. Use of wires of greater diameters causes frequent wire breakage. A statistical analysis was done to pick up the most probabilistic data from the bank of data obtained from the experiments. Finally, mathematical relationships have been developed between job surface finish with current and voltage within the specified ranges for a few work materials.